Triamcinolone Acetonide and 5-Fluorouracil Intralesional Combination Injection in Keloid Treatment - Jono Hadi Agusni; Eva Krishna Sutedja; Franky Chandra (Faculty of Medicine Universitas Padjadjaran, 2017)
Objective: To evaluate the effectiveness of steroid and 5-fluorouracil (5-FU) injection combination for keloid management.Methods: A 22-year-old female patient was presented with recurrent skin lesions. The skin lesions first appeared 10 years prior to consultation, had been surgically excised, and were given triamcinolone acetonide injection. However, no improvement was observed. A decision was made to use and evaluate treatment using an intralesional 4 mg (0.1 ml of 40 mg/ml) triamcinolone acetonide and 45 mg (0.9 ml of 50 mg/ml ) 5-FU injection combination for 5 weeks.Results: Clinical improvements were observed in the third week as the lesions softened and pruritic sensation dinimished. At the end of the fifth week, improvements in the form of keloid lesion flattening and size reduction were observed.Conclusions: Intralesional injection using a combination of triamcinolone acetonide and 5-fluorouracil is effective for keloid lesion treatment.Keywords: 5-fluorouracil, intralesional injection, keloid, triamcinolone acetonide DOI: 10.15850/ijihs.v5n1.959